Menganalisis Pembelajaran Multikultural Pada Paud - Alimni Alimni; Ade Febrianti Valentina (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The concept of education must be able to meet the urgent needs of the Indonesian people today to reconstruct Indonesia's national culture which consists of ethnic and cultural diversity. In this context, the concept of multicultural education could be an alternative considering that multicultural education looks at society at large in terms of its differences. The multicultural education paradigm includes subjects regarding injustice, poverty, oppression and underdevelopment of minority groups in various social, cultural, economic and educational fields.